Mapping the Phospho-dependent ALK Interactome to Identify Novel Components in ALK Signaling. Issue 23 (19th November 2021) - Aboualizadeh, Farzaneh; Yao, Zhong; Guan, Jikui; Drecun, Luka; Pathmanathan, Shivanthy; Snider, Jamie; Umapathy, Ganesh; Kotlyar, Max; Jurisica, Igor; Palmer, Ruth; Stagljar, Igor
Graphical abstract: Highlights: A MaMTH screen of SH2 proteins for ALK interactors was performed. Thirty novel ALK interactors were identified. ALK/NCK2 interaction and its functional changes were confirmed in neuroblastoma cells. Abstract: Protein-protein interactions (PPIs) play essential roles in Anaplastic Lymphoma Kinase (ALK) signaling. Systematic characterization of ALK interactors helps elucidate novel ALK signaling mechanisms and may aid in the identification of novel therapeutics targeting related diseases. In this study, we used the Mammalian Membrane Two-Hybrid (MaMTH) system to map the phospho-dependent ALK interactome. By screening a library of 86 SH2 domain-containing full length proteins, 30 novel ALK interactors were identified. Many of their interactions are correlated to ALK phosphorylation activity: oncogenic ALK mutations potentiate the interactions and ALK inhibitors attenuate the interactions. Among the novel interactors, NCK2 was further verified in neuroblastoma cells using co-immunoprecipitation. Modulation of ALK activity by addition of inhibitors lead to concomitant changes in the tyrosine phosphorylation status of NCK2 in neuroblastoma cells, strongly supporting the functionality of the ALK/NCK2 interaction. Our study provides a resource list of potential novel ALK signaling components for further study.